Gloss to the judgment of the Provincial Administrative Court in Olsztyn of 4 May 2023, II SA/Ol 235/23 - Zawacka-Klonowska, Dominika (Studia Iuridica Toruniensia, 2024)
The Provincial Administrative Court in Olsztyn, in the judgment of 4 May 2023, II SA/Ol 235/23 ruled that the public administration body in the functional sense, meeting the conditions contained in the Act of September 6, 2001 on access to public information, is obliged to providing public information. In the commented (gloss) judgment, the Court rightly stated that the principal of a non-public school is not a public administration body in the systemic sense, but a public administration body in the functional sense. In addition, the headmaster of non-public school is not a public authority within the meaning of the Act on Access to Public Information, which means that his decision refusing to disclosed public information cannot be appealed, only a request for reconsideration of the case. Thus, the Court recognized the administrative decision issued by the founding body as grossly infringing the law and issued without a legal basis, as it was not entitled to consider an appeal against the decision issued by the headmaster of a non-public school.